2010
DOI: 10.1093/chromsci/48.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nimodipine in Human Plasma by HPLC-ESI-MS and Its Application to a Bioequivalence Study

Abstract: A simple, specific, and precise liquid chromatographic-electrospray ionization mass spectrometric (LC-ESI-MS) method has been developed for determination of nimodipine concentration in human plasma. The method involves the addition of 200 microL of saturated sodium bicarbonate (NaHCO(3)) solution to plasma to improve the extraction recovery, liquid-liquid extraction of nimodipine from plasma samples with anhydrous diethyl ether, simple reversed-phase chromatography, and ESI mass spectrometric detection in nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…Calculated mean plasma concentrations of NIM were within ±15% of the nominal concentrations for both LLOQ and high QCs in all the experimental conditions, in line with previously reported data [9][10][11][12][13]. From previous literature, stored plasma samples at < −50 • C proved stable for NIM up to 21 days (10).…”
Section: Assay Performance and Validationsupporting
confidence: 90%
See 2 more Smart Citations
“…Calculated mean plasma concentrations of NIM were within ±15% of the nominal concentrations for both LLOQ and high QCs in all the experimental conditions, in line with previously reported data [9][10][11][12][13]. From previous literature, stored plasma samples at < −50 • C proved stable for NIM up to 21 days (10).…”
Section: Assay Performance and Validationsupporting
confidence: 90%
“…Moreover, compared with the HPLC-MS/MS methods reported so far for the quantitation of NIM in human plasma [9][10][11][12][13], this assay presents two main advantages: it significantly simplifies sample pretreatment, by omitting timeconsuming LLE, avoiding multiple-step sample pretreatment, thus reducing the risks of analytical errors; it employs lower plasma volumes (250 L vs 0.3-1 mL) with comparable LLOQ (0.4 ng/mL vs 0.1-0.5 ng/mL). The method's quantitation range for NIM in both plasma and CSF is adequate for therapeutic drug monitoring in SAH patients at recommended oral and parenteral drug dosages [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo target experiment, for DOC distribution analysis, compared to liquid–liquid anhydrous diethyl ether extraction method [28], we found tissue sample extracted by low toxicity tert-butyl methyl ether can be blown dry easily by nitrogen, and the higher DOC extraction rate in tissue was acquired [24]. Because of the two compartment model of drug distribution, after tail intravenous injection, nanomedicines were distributed immediately in central compartment of organs with abundant blood supply such as liver, heart, kidney and so on, concentration of DOC dropped fastly following with accelerated blood flow, and then nanomedicines were distributed slowly in peripheral compartment of organs with less blood flow such as skin, fat, bone and so on, and GFP expression in vivo was similar to DOC distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated the in vivo applications for NPC therapy. Using a DOC distribution analysis, compared with the liquid-liquid anhydrous diethyl ether extraction method (25), it was demonstrated that tissue samples extracted by low-toxicity tert-butyl methyl ether are easily dried by nitrogen, acquiring an increased DOC extraction rate (26). Due to its size, the nanomedicine is easily delivered to the tumor cell, and accumulates in tumor tissues for enhanced permeability and retention (27,28).…”
Section: Discussionmentioning
confidence: 99%